The Role of Environmental-Based Education in Encouraging Students' Ecological Awareness - Raditya, Raditya Santoso; Minazuki, Unohana; Brodie, Dylan (Journal Sains and Education, 2025)
This study explores the strategic role of environmental-based education in enhancing students' ecological awareness. The implementation of this education involves integrating environmental concepts into both formal curricula and non-formal activities, utilizing an experiential learning approach. Through active participation in hands-on activities such as waste management, tree planting, and environmental projects, students develop ecological literacy comprising knowledge, awareness, and real-world actions to preserve the environment.The positive impacts of environmental education are evident in the increased understanding of environmental issues and the cultivation of critical thinking and pro-environmental behavior in daily life. However, challenges remain, such as limited resources, inadequate teacher training, and low community involvement. Proposed solutions include enhancing teacher capacity, providing necessary resources, fostering multi-stakeholder collaboration, running public awareness campaigns, and integrating environmental education into national policies.